Chk1 loss creates replication barriers that compromise cell survival independently of excess origin firing - González Besteiro, Marina A; Calzetta, Nicolás L; Loureiro, Sofía M; Habif, Martín; Bétous, Rémy; Pillaire, Marie‐Jeanne; Maffia, Antonio; Sabbioneda, Simone; Hoffmann, Jean‐Sébastien; Gottifredi, Vanesa (The EMBO journal, 2019)
The effectiveness of checkpoint kinase 1 (Chk1) inhibitors at killing cancer cells is considered to be fully dependent on their effect on DNA replication initiation. Chk1 inhibition boosts origin firing, presumably limiting the availability of nucleotides and in turn provoking the slowdown and subsequent collapse of forks, thus decreasing cell viability. Here we show that slow fork progression in Chk1‐inhibited cells is not an indirect effect of excess new origin firing. Instead, fork slowdown results from the accumulation of replication barriers, whose bypass is impeded by CDK‐dependent phosphorylation of the specialized DNA polymerase eta (Polη). Also in contrast to the linear model, the accumulation of DNA damage in Chk1‐deficient cells depends on origin density but is largely independent of fork speed. Notwithstanding this, origin dysregulation contributes only mildly to the poor proliferation rates of Chk1‐depleted cells. Moreover, elimination of replication barriers by downregulation of helicase components, but not their bypass by Polη, improves cell survival. Our results thus shed light on the molecular basis of the sensitivity of tumors to Chk1 inhibition. Synopsis Checkpoint Kinase 1 (Chk1) controls new origin firing and replication fork progression by independent mechanisms. In Chk1‐deficient cells, both DNA damage response defects and generation of replication barriers synergize to promote cell death. Excess chromatin association of replicative helicase cofactor CDC45 in Chk1‐deficient cells creates replication barriers. Replication roadblocks slow down fork elongation in Chk1‐deficient cells. Slow fork elongation in Chk1‐deficient cells is not causally related to surplus new origin firing. Replication barriers compromise survival of Chk1‐deficient cells. Graphical Abstract Chk1 inhibition sensitizes cells through distinct mechanisms, causing DNA damage by affecting origin density and impeding replication fork progression via excess MCM helicase cofactor loading.